MANAGEMET OF INFEIOR TURBINATE HYPERTROPHY, COMPARISON BETWEEN TRIMMING OF INFERIOR TURBINATES AND SUBMUCOSAL DIATHERMY IN SAME PATIENT - Nassir, Thana Hikmat (Journal of the Faculty of Medicine Baghdad, 2005)
Summary: Background: the inferior turbinate is the largest turbinate & it is variable in size due to changes in its submucosal vascular bed. Aim of study: the aim of the study is the compare between trimming of the inferior turbinate and submucosal diathermy in the same patient a management of turbinate hypertrophy. Subjects <6 Methods : 250cases inferior turbinate hypertrophy diagnosed by direct examination of the nose by anterior& posterior rhinoscopy were collected Aanalyzed in Saddam Medical City during 1995 - 2000 . Clinical examination, X-ray finding, regarding the age, operative procedures, patients follow up, their complications & treatment Results: The place of radical trimming of the inferior turbinate in the treatment of chronic rhinitis in this study give better results than other type of turbinate surgery in improving airways of the patients which give 100% patiency. Conclusion: the management of hypertrophic inferior trubinales in chronic remains a matter of the controversy . The place of radical trimming of the inferior turbinate in the treatment of this condition has to be established, detailed analysis is presorted Keywords: trubinales, rhinoscopy, submucosa